The Performative Context of a Convent in its Liturgical and Religious Celebrations. Objects and Practices in the Convent of Sant Antoni i Santa Clara in Barcelona (14th-15th Centuries) - Jornet-Benito, Núria (Quaderni di storia religiosa medievale, 2024)
This study examines the performative and material culture within the convent of Sant Antoni i Santa Clara in Barcelona (14th-15th centuries), focusing on its liturgical and devotional practices. By analysing inventories and expense records, the research explores the role of objects - such as herbs, flowers, textiles, paper decorations, and ritual items - in shaping multisensory religious experiences. These objects served functional, symbolic, and aesthetic purposes, contributing to the community’s agency and its interaction with sacred spaces. The study highlights the nuns’ active participation in crafting and arranging these items, revealing their dual role as creators and participants in rituals. This exploration enriches the understanding of female monastic culture, illustrating how objects and practices conferred a distinctive identity on the Poor Clares’ spiritual life.